Preparation and characterization of nano crystalline structures on CK60 steel by drilling method - Nosrati, Shohreh (2013)
Drilling as a surface severe plastic deformation (SSPD) method has been applied to commercial CK60 steel plate to create a nano crystalline (NC) structured layer. In the present study, the CK60 steel plate has been quenched in room temperature water from 950 °C and tempered at 350°C for one hour. Drilling was done with use of a Ti-oxide coated drilling bit at 5, 10, 15 and 20 m/min cutting speeds. The microstructure of the samples was studied by an Optical Microscope and by a field emission scanning electron microscope (FESEM). The formation of an NC layer having a grain size in the order of 50 nm was confirmed by SEM observation and by applying the Hall-Petch formula on the samples drilled at a 20 m/min speed. The fine grain zone created was separated from the base metal structure and clear boundary with a 1 to 10 μm thickness when the drilling speed changed from 15 to 20 m/min. The result of the micro-hardness test determined that the hardness of the surface NC layer increased by more than twice compared with the coarse grain structure of the base metal. The annealing test on the nano crystallized samples in the range 400 to 650 °C showed that the NC layer is thermally stable and the micro-hardness of the surface layer showed a small decrease after 1 hr tempering at 650 °C from 9.8 to 9.1 GPa.